Knowledge and practice regarding pulmonary tuberculosis among private practitioners - Basu, M; Sinha, D; Das, P; Roy, B; Biswas, S; Chattopadhyay, S (Indian Journal of Community Health, 2013)
Background: India leads the world in its burden of tuberculosis (TB). General practitioners are the backbone of health care system. Objective: To assess the knowledge and practice of the allopathic private practitioners regarding TB. Method: In June 2012– October 2012, a cross-sectional study was conducted in West Bengal, India among 180 private practitioners who treat TB patients; using a self-administered semi-structured questionnaire. Results: About 58.3 % and 56.7 % study population knew full form of RNTCP (Revised National Tuberculosis Control Program) and DOTS (Directly Observed Treatment Short Course) respectively. The correct modes of transmission were expressed by 75.0 % of them. The most common symptom of TB was rightly answered by 46.7 %. About 43.3 % and 33.3 % replied correctly about number of sputum samples collected and timing of collection. More than half participants knew number of categories and 8.3 % knew categorisation correctly. About 66.7 % could correctly state the names of recommended 1st line anti-TB drugs; frequency of drug administration told correctly by 68.3 %. Very few Private Practitioners (PPs) knew treatment regimens correctly for each category. Almost all participants knew that treatment under DOTS was given supervised. About 78.3 % PPs expressed correctly that treatment for TB was given in two phases; the duration of treatment of 6-8 months was stated by 53.3 %. Conclusion: Many gaps were found in the knowledge and practices of PPs regarding Tuberculosis. PPs should be properly trained and sensitized to use RNTCP guidelines.